(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
The article examines the philosophical foundations of the informatization process as a key factor in 21st-century civilization. Drawing on historical and contemporary philosophical traditions, it analyzes the ontological and communicative interpretations of information, from ancient philosophy to modern thinkers such as Wiener, Shannon, Floridi, Habermas, Luhmann, Bell, and Toffler. The study highlights the transition from technical to socio-philosophical understanding of information and emphasizes the transformative impact of informatization on society, while offering critical remarks on optimistic assumptions and real-world challenges such as manipulation and information colonialism. The analysis reveals that informatization functions as a mechanism for societal self-renewal, akin to a circulatory system, with significant implications for social structure, consciousness, and global development.